2014
DOI: 10.1007/s40475-014-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Defined Subunit Vaccines for the Prevention of Leishmaniasis

Abstract: Infection with Leishmania parasites can cause disease across a range of clinical manifestations and outcomes. Given the practical difficulties in maintaining vector control programs, vaccination is likely the only way in which the sustained reduction or elimination of the leishmaniases can be achieved. In this review, we focus on the development of second-generation vaccines with emphasis on defined subunit vaccines using recombinant expression techniques. We highlight particular antigens that have provided pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…In Iran, non-healing cases further complicated the feasibility of the widespread use of Leishmanization as it was practiced in the 1980s ( 28 , 33 – 35 ). While leishmanization is no longer widely practiced, the threat of leishmaniasis remains, and intensive investigation is under way to develop killed, naturally attenuated or genetically modified live parasites, or subunit vaccines that replicate the protection mediated by Leishmanization ( 36 ). However, evidence from both C57BL/6 and BALB/c experimental mouse models has shown that a key factor in the efficacy of leishmanization is the persistence of the parasite following inoculation ( 37 39 ).…”
Section: Leishmanization and The Role Of Parasite Persistence In Natumentioning
confidence: 99%
“…In Iran, non-healing cases further complicated the feasibility of the widespread use of Leishmanization as it was practiced in the 1980s ( 28 , 33 – 35 ). While leishmanization is no longer widely practiced, the threat of leishmaniasis remains, and intensive investigation is under way to develop killed, naturally attenuated or genetically modified live parasites, or subunit vaccines that replicate the protection mediated by Leishmanization ( 36 ). However, evidence from both C57BL/6 and BALB/c experimental mouse models has shown that a key factor in the efficacy of leishmanization is the persistence of the parasite following inoculation ( 37 39 ).…”
Section: Leishmanization and The Role Of Parasite Persistence In Natumentioning
confidence: 99%
“…Therefore, despite of numerous recombinant proteins that have been suggested as potential vaccine candidates, to date barely few have reached to clinical trials (107). Similarly, DNA vaccine faces problems in terms of demonstration of safety and efficacy in humans in clinical trial (99).…”
Section: Molecular Approaches To Leishmania Vaccine Developmentmentioning
confidence: 99%
“…Despite these different approaches offer a variable degree of efficacy, several problems still hampers its feasibility due to variations in immunogenicity and due to genetic variation in host as well as in pathogen ( 99 ). Therefore, despite of numerous recombinant proteins that have been suggested as potential vaccine candidates, to date barely few have reached to clinical trials ( 107 ). Similarly, DNA vaccine faces problems in terms of demonstration of safety and efficacy in humans in clinical trial ( 99 ).…”
Section: Molecular Approaches To Leishmania Vaccinmentioning
confidence: 99%
“…donovani infection could be due to several antigens. 89 92 Two criteria that should be considered to initially select potential vaccine antigens include a known antigen that expressed in the disease-causing mammalian stage of the parasite, and the selected adjuvants that elicit a cellular, Th1-biased immune response for the immunizations in humans. 16 Side effects of an adjuvant, such as toxicity, should be noted for the formulation of the vaccine.…”
Section: Introductionmentioning
confidence: 99%